(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Vulvovaginal candidiasis is the infection of the vaginal mucosa and/or vulva caused by the Candida species, a gram-positive yeast-like fungus. It is the second most common vulvovaginal infection characterized by thick-curdy white-cottage-cheese type vaginal discharge and intense vulvovaginal pruritus. Symptomatically vulvovaginal candidiasis can be compared with Slaishmiki yonivyapat in Ayurveda, the line of management of which is the use of Ruksha and Ushna aushadha. Local application of gel has the advantages of easy administration, more bioavailability of drugs, and prolonged retention without much local irritation. The classical Guduchi-Triphala-Danti pariseka yoga, mentioned in Yonivyapat chikitsa has been modified into a gel form, facilitating self-administration by women. Methodology: Here is a case report of a 31-year-old multiparous woman who presented with complaints of curdy white vaginal discharge associated with itching over the vulvar region for the last 6 months. She was diagnosed with vulvovaginal candidiasis by vaginal swab culture. Intervention with Guduchi-Triphala-Danti gel was carried out for 14 days for 2 consecutive cycles excluding days of menstruation and followed up after the next 30 days without medication. Results: After completion of the treatment protocol there was substantial relief of symptoms like curdy white vaginal discharge and itching over the vulvar region, wet-mount microscopy was negative for pseudohyphae, and the vaginal swab culture showed no growth. Conclusion: Local application of Guduchi-Triphala-Danti gel was found to be effective in the management of vulvovaginal candidiasis.